2013
DOI: 10.1002/jmri.24171
|View full text |Cite
|
Sign up to set email alerts
|

MR characterization of hepatic storage iron in transfusional iron overload

Abstract: Purpose To quantify the two principal forms of hepatic storage iron, diffuse, soluble iron (primarily ferritin), and aggregated, insoluble iron (primarily hemosiderin) using a new MRI method in patients with transfusional iron overload. Materials and Methods Six healthy volunteers and twenty patients with transfusion-dependent thalassemia syndromes and iron overload were examined. Ferritin- and hemosiderin-like iron were determined based on the measurement of two distinct relaxation parameters: the “reduced”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
0
26
1
Order By: Relevance
“…The other possible issue with using R2 calibration of St Pierre et al is that R2 was measured using a single spin echo sequence. In patients with high levels of iron, particularly high levels of hemosiderin (which aggregates into larger particles), R2 measured using a fast spin echo sequence is dependent on echo spacing . However, the maximum iron level for the patients included in our study was less than 2.5 mg/g.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The other possible issue with using R2 calibration of St Pierre et al is that R2 was measured using a single spin echo sequence. In patients with high levels of iron, particularly high levels of hemosiderin (which aggregates into larger particles), R2 measured using a fast spin echo sequence is dependent on echo spacing . However, the maximum iron level for the patients included in our study was less than 2.5 mg/g.…”
Section: Discussionmentioning
confidence: 70%
“…However, the maximum iron level for the patients included in our study was less than 2.5 mg/g. The contribution of aggregate, hemosiderin‐like iron at this relatively low level is minimal, much less than 10% . We thus chose not to incorporate any echo‐spacing dependence of R2 into the model reported here.…”
Section: Discussionmentioning
confidence: 99%
“…R2* is often used as a proxy measure of iron overload, but may also be affected by factors such as fibrosis . However, the dephasing effects of iron dominate R2* in vivo, particularly at higher iron levels …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed it is feasible to measure ferritin and hemosiderin iron separately based on non‐monoexponential signal decay models . However, while histologic studies demonstrate that hemosiderin in states of high iron overload accounts for up to 75% of the total iron storage, the mean slow component in our sample was only around 5%, reaching up to 15% in some patients.…”
Section: Discussionmentioning
confidence: 67%